PENGARUH WORK FROM HOME TERHADAP KINERJA AUDITOR DENGAN DIMENSI PERSONALITAS SEBAGAI VARIABEL INTERVENING SELAMA PANDEMI COVID-19 - Zahrotul Jannah; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine how the effect of Work from Home on auditor performance with work motivation and organizational commitment as intervening variables carried out during the COVID-19 pandemic. The population used in this study are auditors who work at KAP in the East Java region who are registered in the Directory of the Indonesian Institute of Certified Public Accountants (IAPI) in 2020 by using purposive sampling technique in sampling. The data collection of this research was done by distributing questionnaires either directly, through the post office, e-mail, and via google form. The data analysis method in this study uses the Structural Equation Model (SEM) using the AMOS 22 program. The results of this study indicate that Work from Home has an effect on work motivation, but Work from Home has no effect on organizational commitment and auditor performance. Then work motivation has an effect on auditor performance. Meanwhile, organizational commitment has no effect on auditor performance.Keywords: Work from Home, COVID-19, auditor performance, motivation, organizational commitment.